2001
DOI: 10.1051/0004-6361:20010746
|View full text |Cite
|
Sign up to set email alerts
|

A new sample of giant radio galaxies from the WENSS survey

Abstract: Abstract.We have used the Westerbork Northern Sky Survey (WENSS) to define a sample of 47 low redshift (z < ∼ 0.4) giant radio galaxies. This is the largest sample yet of such radio sources originating from a single survey. We present radio maps of the newly discovered giants and optical images and spectra of their host galaxies. We present some of their properties and discuss the selection effects. We investigate the distribution of the sources in the radio power -linear size P−D diagram, and how these parame… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
141
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(153 citation statements)
references
References 14 publications
11
141
0
1
Order By: Relevance
“…There is no indication of diffuse emission in total intensity. A circle marks a region around the giant radio galaxy J162740+514012 (see Schoenmakers et al 2001), which contains two lobes that were found to be highly polarized at 325 MHz. The source is found to be polarized in the LOFAR band as well, although at much lower levels.…”
Section: Widefield Image In Total Intensitymentioning
confidence: 99%
“…There is no indication of diffuse emission in total intensity. A circle marks a region around the giant radio galaxy J162740+514012 (see Schoenmakers et al 2001), which contains two lobes that were found to be highly polarized at 325 MHz. The source is found to be polarized in the LOFAR band as well, although at much lower levels.…”
Section: Widefield Image In Total Intensitymentioning
confidence: 99%
“…The source 3C 35 is included in the sample of 47 low redshift (z < 0.4) GRG obtained by Schoenmakers et al (2001) using the Westerbork Northern Sky Survey (WENSS) of the sky above +30 • of declination at 325 MHz (Rengelink et al 1997). The criteria for the sample specified that a candidate GRG must 1 Throughout we adopt H 0 = 71 km s −1 Mpc −1 , Ω m = 0.27, Ω Λ = 0.73 (Spergel et al 2003).…”
Section: Radio Datamentioning
confidence: 99%
“…North HS is a radio hot spot to the north. The combined 1998 and1999 (416) a Redshift of the absorber. Model A assumes that the entire absorption is related to the Galaxy, whiles models B, C, and D assume that the Galactic column is constant at 4:18 Â 10 20 atoms cm À2 and the additional absorption comes from the intervening absorber at a given, fixed redshift.…”
Section: X-ray Emission Within 10mentioning
confidence: 99%
“…Until recently, most GPS/CSS sources were thought to be very compact, with the radio emission contained within $1-10 kpc of the core. About $25% of GPS/CSS sources exhibit faint extended radio emission on scales larger than the size of the host galaxy Stanghellini et al 1990;O'Dea 1998;Fanti et al 2001), with only a few sources showing any radio structures on Mpc scales (Schoenmakers et al 1999;Siemiginowska et al 2002;Marecki et al 2003). This extended radio emission is amorphous or jetlike, but is usually hard to classify because it is weak.…”
Section: Introductionmentioning
confidence: 99%